Analisis Semantik terhadap Kata Tarbiyah dan Derivasinya dalam Hadis: Implikasi dalam Pendidikan dan Pembelajaran: A Semantic Analysis of the Term Tarbiyah and Its Derivatives in Hadith: Implications for Education and Learning - Ahmad Syaripudin; Samsuddin, Samsuddin; Ali Maulida; Iskandar, Iskandar (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
This study examines the semantic meaning of the term tarbiyah and its various derivatives in the Prophetic hadith, as well as their implications for the concepts of Islamic education and learning. Although the term tarbiyah has been widely employed in contemporary Islamic educational discourse, prevailing interpretations often rely primarily on terminological definitions without tracing its lexical and contextual semantic structures within hadith as an authoritative primary source of Islam. This study aims to analyze the etymological roots, derivative forms, and semantic expansions of tarbiyah in hadith, including verbal forms such as tarubbu, yurabbī, yarubbānī, and the expression yurabbī al-nās, as well as nominal forms such as rabb, rabbuhā, and rabbāniyyīn. The research adopts a library-based qualitative approach, employing semantic-linguistic analysis and the taḥlīlī method to examine relevant hadith texts. The findings reveal that the concept of tarbiyah in hadith encompasses six core meanings: (1) preservation and care (ḥifẓ wa riʿāyah), (2) management and development (tanmiyah wa ṣiyānah), (3) education and instruction (taʿlīm wa taʾdīb), (4) guidance and leadership (taujīh wa siyādah), (5) perfection and cultivation (takmīl wa inhmāk), and (6) gradual educational development (tadarruj fī al-taʿlīm). These findings affirm that tarbiyah in hadith is not merely cognitive in nature but represents a comprehensive process that progressively nurtures human potential toward moral and ethical perfection. This study contributes to strengthening the conceptual foundations of Islamic education by restoring the meaning of tarbiyah to its semantic roots and prophetic praxis.